TWO-PARAMETER GAMMA DISTRIBUTION AND LOG NORMAL DISTRIBUTION FOR DERIVATION OF SYNTHETIC UNIT HYDROGRAPH (Journal of Engineering, 2011)
Most available methods for unit hydrographs (SUH) derivation involve manual, subjective fitting ofa hydrograph through a few data points. The use of probability distributions for the derivation of synthetichydrographs had received much attention because of its similarity with unit hydrograph properties. In thispaper, the use of two flexible probability distributions is presented. For each distribution the unknownparameters were derived in terms of the time to peak(tp), and the peak discharge(Qp). A simple Matlabprogram is prepared for calculating these parameters and their validity was checked using comparisonwith field data. Application to field data shows that the gamma and lognormal distributions had fit well.